False positivity of magnetic resonance imaging under the effect of granulocyte-colony stimulating factor in a child with leukemia - Cakir, Fatma Betul; Baysal, Begumhan; Dogan, Oner (Contemporary Oncology/Współczesna Onkologia, 2013)
Granulocyte-colony stimulating factor (G-CSF) increases the proliferation and maturation of committed polymorphonuclear leukocyte precursors, as well as the function of mature polymorphonuclear leukocytes. It has previously been shown in pediatric patients that G-CSF induces reconversion of fatty bone marrow to hematopoietic bone marrow in the pelvis and lower extremities that is detectable by magnetic resonance imaging (MRI). Here, we report a 13-year-old Burkitt leukemia patient with bone pain while he was in remission. He was on G-CSF after cessation of high-dose and low-dose cytarabine chemotherapy. He was suspected to have a leukemia relapse. Pelvic MRI was consistent with leukemic infiltration. However, the pathology of bone marrow biopsy resulted in normal findings. Thus it was suggested that concurrent administration of G-CSF could be the causative agent for both bone pain and false-positive MRI findings. The control MRI after interruption of G-CSF revealed normal findings. In conclusion, radiologists should be informed about the type of therapy, including G-CSF administration, in order to overcome misinterpretation of bone marrow MRI.